For all positive integers k , define f ( k ) = k 2 + k + 1 . Compute the largest positive integer n such that 2 0 1 5 f ( 1 2 ) f ( 2 2 ) ⋯ f ( n 2 ) ≥ ( f ( 1 ) f ( 2 ) ⋯ f ( n ) ) 2 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
same method. you could just have used x ≤ 2 − 1 + 1 + 4 ∗ 2 0 1 4
Exactly Same Way.
Problem Loading...
Note Loading...
Set Loading...
I claim that f ( n 2 ) = f ( n ) f ( n − 1 ) for all n ≥ 1 . To prove this, write f ( n 2 ) = n 4 + n 2 + 1 = ( n 2 + 1 ) 2 − n 2 = ( n 2 − n + 1 ) ( n 2 + n + 1 ) . Now remark that f ( n − 1 ) = ( n − 1 ) 2 + ( n − 1 ) + 1 = n 2 − n + 1 , so we indeed have f ( n 2 ) = f ( n ) f ( n − 1 ) as desired.
As a result, dividing through by f ( 1 2 ) f ( 2 2 ) … f ( n 2 ) and engaging in rampant cancellation yields 2 0 1 5 ≥ f ( 1 2 ) f ( 2 2 ) … f ( n 2 ) f ( 1 ) 2 ⋅ f ( 2 ) 2 ⋅ … ⋅ f ( n ) 2 = [ f ( 0 ) f ( 1 ) ] [ f ( 1 ) f ( 2 ) ] [ f ( 2 ) f ( 3 ) ] … [ f ( n − 1 ) f ( n ) ] f ( 1 ) 2 f ( 2 ) 2 … f ( n ) 2 = f ( 0 ) f ( 1 ) 2 f ( 2 ) 2 … f ( n − 1 ) 2 f ( n ) f ( 1 ) 2 f ( 2 ) 2 … f ( n ) 2 = f ( 0 ) f ( n ) = n 2 + n + 1 . Hence it suffices to find the smallest n such that 2 0 1 5 ≥ n 2 + n + 1 . To do this, remark that n 2 + n + 1 ≈ n ( n + 1 ) . From here, one can see that 4 4 ⋅ 4 5 = 1 9 8 0 and that 4 5 ⋅ 4 6 is too large, so n = 4 4 is the largest value of n which makes the inequality true.